PASAR TENAGA KERJA INKLUSIF DAN PEKERJAAN AFIRMATIF UNTUK PENYANDANG DISABILITAS - Daniel Jesayanto Jaya; Taufik Wisnu Saputra; Andry Ananda Putra Tanggu Mara (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
An inclusive labour market emphasizes equal opportunities and fair treatment for all individuals, including persons with disabilities, with the aim of optimizing the potential of the workforce, increasing innovation, productivity, and economic growth. In Indonesia, inclusive policies have been implemented through various laws and regulations that support the rights of persons with disabilities to obtain decent work. Nonetheless, challenges in the form of discrimination and lack of supporting infrastructure are still significant. Disabled people's organizations (DPOs) play an important role in economic empowerment through skills training and entrepreneurship. This training covers areas such as screen printing, electronics, computers and weaving, as well as social assistance for small businesses. The types of jobs available to people with disabilities include operators, customer service, telemarketing, teachers, and administration. Awareness and effective policies are needed to create a truly inclusive workplace in Indonesia. With sustained commitment from all parties, Indonesia can respect and protect the rights of persons with disabilities, ensure equal and fair access to employment opportunities, and harness their full potential for nation-building.